ANALISIS KEMAMPUAN BERPIKIR REFLEKTIF DAN ANALITIK PESERTA DIDIK SMP DALAM MENYELESAIKAN SOAL MODEL PROGRAMME FOR INTERNATIONAL STUDENT ASSESSMENT (PISA) - Hadimu, Hasan Bashri; Laurens, Theresia; Moma, La (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2020)
During this time, reflective thinking and analytical skills have not been one of the objectives of mathematics and learners have not demonstrated reflective activity and analytic learning. The ability of the students ' reflective thinking and analytics is an important aspect to be examined and developed so that the learner's math learning is more optimal. The study aims to describe the ability of the students ' reflective thinking and analytic of junior high school in solving the Programme for International Student Assessment (PISA) model. This research is a qualitative descriptive study describing the reflective thinking skills and analytical students of junior high school in solving the Programme for International Student Assessment (PISA) model. The subject in this study is a class IX student consisting of three learners with the details of each of the 1 learners with reflective thinking skills, 1 student with analytic thinking skills and 1 student with reflective and analytical thinking skills. The data collection techniques used are tests of reflective thinking and analytical skills as well as interviews. Test Data and interviews are analyzed based on indicators that meet the ability of reflective thinking and analytical thinking skills. Data analysis techniques refer to the Miles and Hiberman concepts which include data reduction, data presentation, and conclusion withdrawal. Data validity techniques use observer persistence, triangulation time and peer checking. The results of the study provide conclusions: 1) Subject 1 meets the indicator of the reflective thinking ability, subject 1 able to the reacting phase, comparing, less in the contemplating phase: 2) Subject 2 meets the analytical thinking ability indicator, subject 2 is capable at would phase, organizing and attributing: 3) Subject 3 meets the indicator of reflective thinking capabilities capable of the reacting, comparing, contemplating and subject 3, organizing and attributing